We are given the equation:
\[
\left( \frac{0.007}{0.049} + \frac{0.049}{0.007} \right)^2 = \frac{2500}{K - 1}.
\]
Step 1: First, simplify the expression inside the brackets:
\[
\frac{0.007}{0.049} = \frac{7}{49} = \frac{1}{7}, \quad \frac{0.049}{0.007} = \frac{49}{7} = 7.
\]
So,
\[
\frac{1}{7} + 7 = \frac{1}{7} + \frac{49}{7} = \frac{50}{7}.
\]
Step 2: Now, square the result:
\[
\left( \frac{50}{7} \right)^2 = \frac{2500}{49}.
\]
Step 3: Substitute this into the equation:
\[
\frac{2500}{49} = \frac{2500}{K - 1}.
\]
By cross-multiplying:
\[
49(K - 1) = 2500.
\]
\[
K - 1 = \frac{2500}{49}.
\]
Step 4: Simplify the right-hand side:
\[
K - 1 = 51.
\]
Step 5: Finally, solve for \( k \):
\[
K = 52.
\]
Thus, the value of \( k \) is \( 50 \).